IDENTIFIKASI DAN MINIMASI WASTE DENGAN PENERAPAN LEAN MANUFACTURING PADA PROSES PRODUKSI CIRENG DI PT BRECXELLE BERKAH UNITI - Firizky Tania Dwi Wanda, (2022)
PT Brecxelle Berkah Uniti is one of company in the the cireng food industry who pays attention to the details of the process in each of its production lines. However, in the production process, waste is found which can cause losses to the company. Based on the results of observations and the 7 waste questionnaires, it was found that the 3 most dominant wastes were defects, waiting, and excessive transportation. Waste of defects that occur such as cireng are shapeless, destroyed, and do not pass through the metal detector machine. Waste of waiting occurs during the cooling process, when starting the engine, and waiting for the pressing process. Waste of transportation occurs due to circular and non-consecutive process flows. This research aims to minimize production time and increase production result by simulating the cireng production process of PT Brecxelle Berkah Uniti using the Lean Manufacturing and System Simulation method. Based on the simulation results with the proposed improvements, the results obtained from the simulation were that the total production lead time was reduced by 657,97 seconds or 10,97 minutes from 2426.77 seconds or 40.45 minutes to 1768,80 seconds or 29,48 minutes. The NVA and NNVA time on FVSM also decreased by 648,53 seconds or 10.81 minutes from the activity time on CVSM. Based on the simulation results, production results increased by 80% after the proposed improvements, from 4,671,945 pcs per month to 8.429.679 pcs per month.